Methodological Interaction between Experimental and Computer Philosophy - Ekaterina A. Alekseeva (RUDN Journal of Philosophy)
The study is devoted to the problem of the relationship between the methods of two contemporary philosophical trends: experimental and computer philosophy. Both of these trends are distinguished by the fact that they depart from the principles of “armchair” philosophy, although they do not break with it completely, turn to empirical data, etc. The key principles of experimental philosophy are considered, which allow integrating the methodological structure of experimental philosophical research with approaches in the field of computer philosophy. It is also demonstrated that with the help of computer philosophy, such classical philosophical methods as conceptual analysis and thought experiments can be transformed. This, among other things, allows integrating them into experimental philosophical research. Four groups of computer technologies are distinguished that can be used in conjunction with philosophical methods. These are data analysis technologies, computer modeling (multi-agent systems, etc.), generative technologies, computer games. In the context of philosophical research, the results obtained with the help of these technological tools receive a semantic interpretation. This paper proposes the problematic of a potential experimental philosophical study devoted to the problem of confirmation/proof in the field of evidence-based medicine and medical activity. Options are offered for how the methods of computational philosophy could be used to conduct such a study.